Decentralization and Regional Autonomy: A Historical and Conceptual Review - Prabowo, Andek; Tjenreng, Muhammad Baharuddin Zubakhrum (International Journal of Science and Society, 2025)
The implementation of decentralization and regional autonomy in Indonesia still faces various challenges, although it has experienced significant developments. Various laws and government policies have been implemented to strengthen regional governance and improve community welfare. However, in practice, there are still obstacles in implementing these policies, such as the imbalance of authority between the central and regional governments and problems in resource management. Along with the dynamics of change from the Old Order era to the Reformation Era, decentralization continues to undergo adjustments to be more effective. Therefore, this study seeks to provide a deeper understanding of the development of decentralization and regional autonomy in Indonesia and to be a reference for improving future policies.